Political Communication of Ulama on Social Media: Discourse Analysis of Ustadz Abdul Somad Lecture on YouTube in the 2019 Presidential Election - Hopizal Wadi; Laesa Diniaty; Fahrurrazi Fahrurrazi (Kawanua International Journal of Multicultural Studies, 2021)
Da'wah and technological advances are inseparable, but this is a foothold in the concept of contemporary da'wah that is easily accepted by today's society. The presence of new media is utilized by everyone who has political interests, from politicians, party people even to clerics to convey a politically weighted message. One of them is ustad Abdul Somad's discourse that uses new media to preach and package symbolically politically charged messages. In analyzing ustad Abdul Somad's political discourse on social media, especially YouTube, the author used the knife of norman fairclough's critical discourse analysis theory to dismantle the practice of lecture discourse. The results of this study show that the discourse of Ustadz Abdul Somad lectures has a political content that is discussed in a symbolic way. The clarity of the symbol is part of the message of political communication, because political communication is not only in verbal language but can be packaged with nonverbal language. Ustadz Abdul Somad on the political stage has the legitimacy to give a message that persuades the public of his choice, because Ustadz Abdul Somad is not just a da'i but not apart from social status that easily approaches and mobilizes the community. Therefore, the representation of symbols will form an identity, then the symbolic message delivered will be believed to be a political message because it is spoken in an election year. The discourse of Ustadz Abdul Somad's lectures could not be separated from the political content to influence the community packed with symbolic messages in his lectures.